Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0181081
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin resistance in non-small cell lung cancer cells is associated with an abrogation of cisplatin-induced G2/M cell cycle arrest

Abstract: The efficacy of cisplatin-based chemotherapy in cancer is limited by the occurrence of innate and acquired drug resistance. In order to better understand the mechanisms underlying acquired cisplatin resistance, we have compared the adenocarcinoma-derived non-small cell lung cancer (NSCLC) cell line A549 and its cisplatin-resistant sub-line A549rCDDP2000 with regard to cisplatin resistance mechanisms including cellular platinum accumulation, DNA-adduct formation, cell cycle alterations, apoptosis induction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 50 publications
8
107
1
Order By: Relevance
“…For that, we studied the effect of 3a' on the cell cycle phase distribution ( Figure 3) and apoptosis (Figure4)ofS W620-O and SW620-MPR cells. Moreover,w hereas cisplatin appeared to inducea significant G2/M arrest, consistent with previouso bservations, [23] 3a' only occasioned am inor reorganizationb etween the Sand G2/M subpopulations, with no effect on the percentage of cells at G0/G1. Moreover,w hereas cisplatin appeared to inducea significant G2/M arrest, consistent with previouso bservations, [23] 3a' only occasioned am inor reorganizationb etween the Sand G2/M subpopulations, with no effect on the percentage of cells at G0/G1.…”
supporting
confidence: 89%
“…For that, we studied the effect of 3a' on the cell cycle phase distribution ( Figure 3) and apoptosis (Figure4)ofS W620-O and SW620-MPR cells. Moreover,w hereas cisplatin appeared to inducea significant G2/M arrest, consistent with previouso bservations, [23] 3a' only occasioned am inor reorganizationb etween the Sand G2/M subpopulations, with no effect on the percentage of cells at G0/G1. Moreover,w hereas cisplatin appeared to inducea significant G2/M arrest, consistent with previouso bservations, [23] 3a' only occasioned am inor reorganizationb etween the Sand G2/M subpopulations, with no effect on the percentage of cells at G0/G1.…”
supporting
confidence: 89%
“…However, the exact mechanism(s) underlying the emergence of drug resistance remains poorly understood and a bewildering plethora of targets have been implicated in different cancer types. For example, in NSCLC alone, dysregulation of genes involved in cell cycle arrest and apoptosis namely, mouse double minute 2 homolog (MDM2), xeroderma pigmentosum complementation group C, stress inducible protein and p21 (Sarin et al, 2017), cytoplasmic RAP1 that alters NF-κB signaling, upregulation of antiapoptotic factor BCL-2 (Xiao et al, 2017), enhanced Stat3 and Akt phosphorylation, high expression of survivin (Hu et al, 2016), hypoxia factor HIF-1α and mutant p53 (Deben et al, 2018), have been implicated in cisplatin resistance. Furthermore, although changes in administration schedules, choice of methods, and frequency of toxicity monitoring have all contributed to incremental improvements, chemoresistance limits the clinical utility of cisplatin (Fennell et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These results confirmed that the combination of DOX and CDDP effectively inhibited MDR development in A549 tumors, consistent with the cell test results in vitro (Figures 2F and 3F). [ 51,52 ]…”
Section: Resultsmentioning
confidence: 99%